Viral gastroenteritis in children: modern concepts of epidemiology and prevention - K. D. Ermolenko; Yu. V. Lobzin; N. V. Gonchar (Журнал инфектологии)
More than 60 original articles and reviews were analyzed in order to study the current state of the epidemiology and prevention of acute intestinal infections (AII) of viral etiology in the world. Interest in a problem of viral AII is determined by their widest prevalence and huge costs associated with the elimination of their consequences. There are at least eight families of viruses that are the cause of acute gastroenteritis. The expansion of the ideas on the epidemiology of viral gastroenteritis has made a significant contribution to increasing the availability of modern diagnostic methods. Leading positions in the etiological diagnosis of viral diarrhea belong to the polymerase chain reaction. The structure of the viral AII in Russia is comparable with the average global rate. The most important frequency agents are rotaviruses and noroviruses. The article reflects the current trends in the epidemiology of acute viral diarrheal diseases: particularly dominant circulating serotypes of rotavirus and rare serotypes in various regions; seasonal changes of dominant strains of rotaviruses; increased frequency of norovirus gastroenteritis in the structure of the AII and increase mortality of children from norovirus infection. Presents data on the phylogenetic diversity of noroviruses and features of GI and GII circulation of genotypes. After the introduction of mass vaccination against rotaviruses in developed countries increases the share of astroviral and adenoviral infection in the structure of the AII. High frequency of astroviral infection is noticed in people with immunodeficiency. Much attention in article is paid to the increase in incidence and mortality of noroviruses, rise in detection rate of mixed viral and viral-bacterial associations and often registration of rare viruses and animal viruses in children. Presents data on the effectiveness of vaccination against rotaviruses in different regions of the world, the development of new vaccines for the prevention of norovirus gastroenteritis. New knowledge about the epidemiology of viral gastroenteritis will contribute to the development of effective  measures of specific preventive maintenance, based on the introduction of vaccination against the most common serogroups of pathogens and application of vaccines with high immunogenicity.